2010
DOI: 10.1074/jbc.m109.055640
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase Activation, an Early Cellular Response to Acidosis

Abstract: Extracellular acidosis often rapidly causes intracellular acidification, alters ion channel activities, and activates G proteincoupled receptors. In this report, we demonstrated a novel cellular response to acidosis: induction of the zymogen activation of matriptase. Acid-induced matriptase activation is ubiquitous among epithelial and carcinoma cells and is characterized by rapid onset, fast kinetics, and the magnitude of activation seen. Trace amounts of activated matriptase can be detected 1 min after cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 59 publications
2
89
0
Order By: Relevance
“…The skin tissue sections were obtained with written informed consent from Tri-Service General Hospital, National Defense Medical Center under the IRB 099-05-019, approved by TSGHIRB. The specificity of these mAbs and their applications in immunohistochemical staining can be found in our previous studies (Benaud et al, 2001;Chen et al, 2011;Lin et al, 1999;Tseng et al, 2010;Wang et al, 2009). Mouse IgG was used as a negative control and the well-characterized staining at intercellular junctions and the distribution profiles in the epidermal layers (Chen et al, 2013a) were used as criteria for the quality of the immunohistochemical staining of the hair follicles.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The skin tissue sections were obtained with written informed consent from Tri-Service General Hospital, National Defense Medical Center under the IRB 099-05-019, approved by TSGHIRB. The specificity of these mAbs and their applications in immunohistochemical staining can be found in our previous studies (Benaud et al, 2001;Chen et al, 2011;Lin et al, 1999;Tseng et al, 2010;Wang et al, 2009). Mouse IgG was used as a negative control and the well-characterized staining at intercellular junctions and the distribution profiles in the epidermal layers (Chen et al, 2013a) were used as criteria for the quality of the immunohistochemical staining of the hair follicles.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The total matriptase mAbs M24 and M32 recognize both latent and activated forms of human matriptase. M69 mAb is specific for activated matriptase and does not recognize latent matriptase, and M19 mAb specifically recognizes human HAI-1 (Chen et al, 2010b;Lin et al, 1997;Lin et al, 1999;Tseng et al, 2010). HGF protein was detected using a goat polyclonal antibody (Santa Cruz Biotechnology Inc., Santa Cruz, CA) that recognizes the beta subunit of HGF.…”
Section: Antibodiesmentioning
confidence: 99%
“…Matriptase activation can be induced by several nonprotease factors, including sphingosine 1-phosphate in mammary epithelial cells (2), androgens in LNCaP prostate cancer cells (10), and suramin in several matriptase-expressing epithelial and carcinoma cells (12). Aspects of the extracellular environment, such as acidity or the presence of reactive oxygen species, can also stimulate cells to activate matriptase (11,36). Once activated, matriptase must apparently immediately act on its substrates, since free-active matriptase has a very short half-life.…”
mentioning
confidence: 99%
“…Matriptase gene mutations lead to ichthyosis as recently reported (Alef et al 2008). Matriptase is immediately activated by exposure to an acidic pH, as it occurs in skin, suggesting that matriptase activation may be a direct response to proton exposure (Tseng et al 2010). Recent evidence showed that during epidermal differentiation, the matriptase-prostasin proteolytic cascade is tightly regulated by two mechanisms, either by prostasin activation temporally coupled to matriptase autoactivation or by the hepatocyte growth factor activator-inhibitor-1(HAI-1), which is rapidly inhibiting not only active matriptase but also active prostasin, resulting in an extremely brief window of opportunity for both active matriptase and active prostasin to act on their substrates (Chen et al 2010).…”
Section: Matriptase and Prostasinmentioning
confidence: 99%